Ethics in Social Science Research in Indonesia - Oey-Gardiner, Mayling; Rahardi, Fandy; Can, Canyon Keanu (Singapore : Springer Nature Singapore : Imprint: Springer, 2023)
This textbook presents ethical guidelines for conducting research in the social sciences, focused on Indonesia. As a country with a fast-growing research environment, the real-life cases of ethical issues that arise in Indonesia can teach both aspiring and established researchers how to approach the complexity of research ethics and dilemmas. With technological advancement affecting how research is conducted, the necessary ethical guidelines for research are also evolving. The instantaneous nature of information movement has made confidentiality in research data more critical than before, and any negligence in protecting research participants has an unprecedented scope of damage. The methods book synthesises hundreds of worldwide ethical guidelines and past issues that social science researchers will find highly relevant. Arranged chronologically to represent each research stage-from research preparation to post-research-the book prepares researchers to mitigate ethical crises. Relevant to all social scientists, both emerging and established, conducting research in Indonesia, this co-published textbook between Springer and OBOR is also relevant to researchers beyond the archipelago. It is also an indispensable teaching resource for lecturers in research methods and ethics across social science disciplines.
Chapter 1. Introduction -- Chapter 2. Before Research -- Chapter 3. Ethics During Research -- Chapter 4. Post-Research -- Chapter 5. Research Misconduct -- Chapter 6. Recommendations.
Keywords: Research -- Methodology; Philosophy and social sciences; Anthropology -- Research; Political science; Education -- Research; Ethics; Research Skills; Philosophy of the Social Sciences; Research Methods in Anthropology; Methodology of Political Science; Research Methods in Education; Moral Philosophy and Applied Ethics